Pengaruh Modal Kerja dan Perputaran Piutang terhadap Profitabilitas Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar Di BEI Tahun 2020-2022 - Stephanie Anni Melissa (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Companies in the food and beverage sector that are listed on the Indonesian Stock Exchange have the same goal as any other company: to maximize earnings. Working capital management and accounts receivable turnover are critical factors that might affect a company's financial performance in this setting. Previous studies have shown that improved management of a company's working capital and receivables may lead to increased earnings. Listed businesses in the food and beverage subsector on the IDX will have their working capital and receivables turnover assessed for their impact on profitability from 2020 to 2022. A quantitative research technique grounded on descriptive methodology is used in this study. The food and beverage industry had a number of IPOs between 2020 and 2022 on the IDX. As supplementary resources, we rely on www.idx.co.id and the company's annual financial report. We used a multiple linear regression test to examine the data and determine the impact of working capital and receivables turnover on profitability at the same time. Data shows that between 2020 and 2022, receivables turnover and working capital together have a major impact on the profitability of IDX-listed food and beverage subsector firms. Improved management of working capital and receivables may lead to higher profitability, according to the research. Future studies should include a larger sample size and more factors to better advise organizational management on financial decision-making.